Characteristics of Tritordeum and evaluation of its potential for cultivation in Poland, with considerations for the nutritional and fodder value of the grains - Różewicz, Marcin; Wyzińska, Marta (Polish Journal of Agronomy, 2021)
After triticale, Tritordeum is the second cereal obtained by means of hybridization. As a new type of cereal, it can be introduced in the long term into cultivation in Polish conditions after conducting scientific research. However, it is necessary to identify its requirements regarding climate, soil conditions as well as agricultural engineering. Since this cereal has a high nutritional value, it may be successfully used in the production of food products with increased nutritional value. At the same time, the grains have a good fodder value, therefore they can also be used for the production of feed for livestock. In this work, a description of Tritordeum and an assessment of the cultivation potential of this crop in Poland are undertaken, with considerations for its nutritional and fodder value, based on the scientific literature.